Des processus interactifs qui façonnent l’intégration d’enseignants formés à l’étranger dans l’école québécoise : entre identification et soumission - Morrissette, Joëlle; Gagnon, Caroline; Malo, Annie (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
This research aims to shed light on the growing phenomenon professional integration of foreign-trained teachers in Quebec school. We invited 12 of them to an individual interview to understand the specifics of their integration process. An inductive analysis attentive to biographical paths and work interactions has led to identify four types of integration process: identification, accommodation, recomposition and submission. Shedding light on these processes shows the disparities between their respective re-socialization contexts of their to the profession. Keywords: foreign-trained teachers, professional integration, work interactions, socialization, working conventions